E-commerce: A taxing regime to tax - Mat Udin, Noraza; Adebayo, Lamidi Wasiu (2015)
E-commerce is a new mechanism to transact business either locally or globally by using the internet or web.In line with the terrific development of e-commerce technology, taxation of e-commerce has also become a major challenge in the world which needs to be addressed seriously.The tax authority has found that the taxation of online transaction is taxing because of the nature of e-commerce and the way it operates.This paper discusses the e-commerce environment including its features and nature which consequently leads to the challenges and difficulties in charging relevant taxes on this kind of business transaction.Discussions on taxation principles and taxes related to e-commerce are also included.In addition, this paper explains various aspects of challenges to tax e-commerce transaction which may cause revenue losses to the Nations.The paper ends with a brief conclusion and recommendation sin order to sustain the competitive advantage of e-commerce.